AGREE II assessments of recent acne treatment guidelines: how well do they reveal trustworthiness as defined by the U.S. Institute of Medicine criteria?3. (29th November 2017) - Eady, E.A.; Layton, A.M.; Sprakel, J.; Arents, B.W.M.; Fedorowicz, Z.; van Zuuren, E.J.
Summary: Background: Up‐to‐date, trustworthy guidelines are a widely relied upon means of promoting excellent patient care. Objectives: To determine the quality of recently published acne treatment guidelines by utilizing the Appraisal of Guidelines for Research and Evaluation (AGREE) II Reporting Checklist, the U.S. Institute of Medicine's (IOM) criteria of trustworthiness, the red flags of Lenzer et al . and CheckUp. Methods: Systematic searches were conducted in bibliographic databases, guideline depositories and using Google to identify acne treatment guidelines published since 2013. Six assessors independently scored each guideline using the AGREE II Reporting Checklist. Guidelines were concomitantly assessed for trustworthiness using the IOM criteria and for the red flags of Lenzer et al ., indicative of potential bias. Updates were screened using CheckUp. Results: Eight guidelines were identified, two of which were updates. Lowest scoring AGREE II domains across all guidelines were applicability (six poor, one fair, one average) and rigour (four poor, one fair, three average). Two of the three highest‐scoring guidelines were developed using AGREE II. No guideline fully met each IOM criterion and all raised at least one red flag indicative of potential bias. One updated guideline did not address seven of 16 items on CheckUp and the other did not address four. Patient involvement in guideline development was minimal. Conclusions: Use of the AGREE II instrument during guideline development did not have as great an effect on guideline quality as might be expected. There is considerable room for improvement in acne treatment guidelines in order to satisfy the IOM trustworthiness criteria and avoid bias. Abstract : What's already known about this topic? Healthcare providers rely on guidelines as trustworthy summaries of clinical evidence that also include recommendations intended to optimize patient care. Two independent critical appraisals of acne treatment guidelines published between 2007 and 2013 using the Appraisal of Guidelines for Research and Evaluation (AGREE) II Reporting Checklist found them to be of variable quality with room for improvement. What does this study add? Acne treatment guidelines published since 2013 were deficient in several key areas, even those developed using the AGREE II instrument. They universally lacked adequate stakeholder involvement, transparency and methodological rigour. Trustworthiness as defined by the U.S. Institute of Medicine criteria was only partially attained. All raised one or more of the red flags of Lenzer et al ., indicative of potential bias. Plain language summary available online